2018
DOI: 10.14419/ijet.v7i2.29.13998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Socio-Demographic Association of Depression, Anxiety and Stress Among University Students

Abstract: Prevalence of Stress, anxiety and depression has been identified to be high among university students which may affect their social and professional lives. The study aims at assessing the prevalence of stress, anxiety and depression among university students and analyzes their association with gender, ethnicity and area of upbringing. The study also intends to identify their coping strategies. This was a cross sectional study utilizing validated questionnaires. It was conducted among a total of 143 university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…DASS 21 Questionnaire: Depression Anxiety Stress Scale (abbreviated as DASS 21) is a 21 self-administered questionnaire rated on a four-point Likert scale measuring the frequency of participants’ experiences over the last week’s duration. This scale was developed by Lovibond et al [ 50 ] and the validation and reliability of this instrument has been established by various researchers [ 51 , 52 ] and has been commonly used to grade the severity of symptoms of anxiety and depression in both clinical and academic settings. [ 51 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DASS 21 Questionnaire: Depression Anxiety Stress Scale (abbreviated as DASS 21) is a 21 self-administered questionnaire rated on a four-point Likert scale measuring the frequency of participants’ experiences over the last week’s duration. This scale was developed by Lovibond et al [ 50 ] and the validation and reliability of this instrument has been established by various researchers [ 51 , 52 ] and has been commonly used to grade the severity of symptoms of anxiety and depression in both clinical and academic settings. [ 51 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…This scale was developed by Lovibond et al [ 50 ] and the validation and reliability of this instrument has been established by various researchers [ 51 , 52 ] and has been commonly used to grade the severity of symptoms of anxiety and depression in both clinical and academic settings. [ 51 , 53 ]. As stated by the content creator, the use of this questionnaire is permissible for all academic purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological distress like depression, anxiety, and stress were also statistically linked with poor levels of HRQoL among healthcare students [7,8,[10][11][12]. These challenges are commonly reported in the literature among healthcare students and to a higher extent among females [1,2,8,13,14]. Previous studies have reported that healthcare students in Jordan have poor lifestyle habits and challenging levels of musculoskeletal, mental health stressors and low levels of HRQoL [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare students are a very important student subgroup that might face unique kinds of stressors related to their academic and clinical activities, financial responsibilities, and social commitments. These stressors might hinder healthcare students' health-related quality of life (HRQoL) and academic progress [5][6][7][8][9]. Psychological distress like depression, anxiety, and stress were also statistically linked with poor levels of HRQoL among healthcare students [7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation